Rom 5.18–19 and Universal Salvation - Bell, Richard H. (New Testament studies, 2002)
Rom 5.18–19 summarises Paul's view of condemnation in Adam and salvation in Christ. Since Paul believes that all human beings participate in Adam's sin and in Christ's ‘righteous act’, a universal salvation is affirmed. This view is clearly at variance with other parts of Romans (not to mention his other extant works). The difference in view could be explained by the fact that Paul in Rom 5.18–19 is using the mythical concept of participation and that he is focusing on the effects of Christ's reconciling act rather than on how the reconciling word is brought to human beings.